Effect of training status on the changes in platelet parameters induced by short–duration exhaustive exercise. (17th February 2016) - Alis, Rafael; Sanchis-Gomar, Fabian; Risso-Ballester, Jennifer; Blesa, Jose R.; Romagnoli, Marco
Abstract: It is now well known that hemostasis is directly involved in the benefits induced by physical activity. It has recently been shown that the baseline mean platelet volume (MPV) may be a predictor of endurance performance. We aimed to explore whether platelet parameters are associated with VO2max as well as running duration and speed in a short-duration exhaustive exercise test. Thirty healthy male subjects (10 sedentary and 20 trained) performed an incremental running test until exhaustion. MPV, platelet distribution width (PDW), platelet (Plt) count, and plateletcrit (Pct) were determined before exercise, immediately after exercise and after 30′ recovery. Training status did not produce any difference in the baseline levels or in the post-exercise increases found in all the parameters tested. VO2max, test duration, and running speed were not correlated with any baseline parameter. Although MPV was found to be a predictor of endurance performance in long-duration exercise, the results of the present study are consistent with the hypothesis that MPV may not be a significant marker of performance in short-duration exhaustive exercise. Likewise, more research is needed to ascertain whether platelet activation is a reliable performance predictor in other exercise settings.